Mapping Female identity in Top Girls by Caryl Churchill (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Caryl Churchill, a celebrated writer, gave cutting edge to theatre with thought-provoking content and innovative structures. In Top Girls Churchill projects, a career driven woman, Marlene who tries to dismantle the oppressive system and reflects upon broader societal dynamics. The play, Top Girls is a statement of how women have been on a receiving platform across ages. History, literature and Art stand witness to how women have been constrained by men. Caryl Churchill explores the path of women's development in different historical periods. Churchill is a writer with change who pens from the real experiences and has the courage to vividly express the same in truest colours. The play shows how women strive hard to claim their own identity. The struggle to break the chains of subjugation and exploitation can be traced back to ancient times. Society believes that women are confined to domestic chores or they are born only to obey their husbands and never to question their authority. In the play, the protagonist Marlene has changed the viewpoint of society by working hard and became a successful woman. Marlene is an ambitious woman who defines and assert their identity. She has the urge to live a life of purpose which is set by her own self.